RELATED BY BLOOD (TO THE QUESTION OF YURIY FED’KOVYCH’S RELATIONS WITH POLAND) - Ковалець, Лідія (Кафедра полоністики Навчально-наукового інституту філології Київського національного університету імені Тараса Шевченка, 2023)
For the first time in literary studies, the topic of relations between the Ukrainian writer, public and cultural figure Yuriy Fed’kovych (1834–1888) and Poland is at the center of a separate scientific observation. Significant documentary material is pointed out: the relevant biographical materials, the artist’s creative heritage, numerous historical and literary publications on certain topics in Polish, as well as translations of Fed’kovych’s writings in Polish. The delin- eation of the source base made it possible to understand that most of it is still scattered, so mostly outdated, and therefore not involved in the study, the latest period in the development of the topic in Polish and Ukrainian literary and sci- entific community remains completely unknown. The article outlines Y. Fed’kovych’s genetic and interpersonal contacts with Poland, remarkable and psychologically complicated with the noble origin of the writer’s father, A. Hordyński de Fedkowicz. The interest of author of “Night Lodging», “Love – Loss» to Polish literature and in general Polish culture, his relationship with the Polish people and so on. The question of the development of Polish motives in the work by Y. Fed’kovych was also raised. The attempt to characterize certain tendencies in the Polish-language literary critical reception of the Ukrainian author, which took place mainly in the 19th century, and in the field of translation was made. Among the literary works, more attention is naturally paid to the study by the Polish writer Abgar-Soltan «Józef Jerzy Hordyński-Fedkowicz, poeta rusiński na Bukowinie» (1892), one of the best monographic works about a Bukovinian who saw the world outside Ukraine. In the desired future may be realized the comprehensive edition of relevant sources and professional study of each of the layers of this important material.

Уперше в літературознавстві тема зв’язків українського письменника та громадсько-культурного діяча Юрія Федьковича (1834–1888) з Польщею виявляється в центрі окремого наукового спостереження. Указано на значний документальний матеріал: відповідні біографічні матеріали, творчу спадщину митця, численні польськомовні історико-літературні публікації визначеної тематики, а також переклади Федь- ковичевих писань польською мовою. Якраз окреслення джерельної бази дало змогу зрозуміти, що велика її частина досі розпорошена, тож переважно неактуалізована, а отже, не залучена до вивчення, цілком недовідомим залишається новітній період в освоєнні теми з боку польської та й української літературно-наукової громадськості. У статті окреслено генетично-контактні зв’язки Ю. Федьковича з Польщею, примітні та психологічно ускладнені шляхетським походженням батька письменника, Ад. Гординського де Федьковича, мовлено про інтерес автора «Нічлігу», «Люби – згуби» до польської літератури та культури загалом, про взаємини його з польською людністю тощо. Порушено також питання про розвиток польських мотивів у творчості Ю. Федьковича, здійснено спробу характеристики певних тенденцій у польськомовній літературно-критичній рецепції українського автора, що мала місце головно у ХІХ ст., та у перекладацькій сфері. Із літературознавчих праць закономірно акцентовано увагу на розвідці польського письменника Абгара-Солтана «Jόzef Jerzy Hordyński-Fedkowicz, poeta rusiński na Bukowinie» (1892), одній із найкращих монографічних праць про буковинця, що побачила світ поза Україною. У бажаній перспективі – збірне видання відповідних джерел і фахове вивчення кожного з пластів цього важливого матеріалу.
СПОРІДНЕНИЙ КРОВНО (до питання про зв’язки Юрія Федьковича з Польщею)
Keywords: Ю. Федькович; Польща / польський; генетичне; взаємозв’язки; літературно-критична праця; переклад; Y. Fed’kovych; Poland / Polish; genetic; relationships; literary-critical work; translation